Electrostatic Tuning of Spray‐Deposited ZnO for Controlled Mobility Enhancement. (30th June 2017) - Zeumault, Andre; Scheideler, William; Subramanian, Vivek
Abstract : Spray‐deposited nanocrystalline ZnO films are produced in order to establish empirical relationships between synthetic conditions and the density of states as a means of achieving electrostatic control. By varying the spray‐pyrolysis deposition conditions, i.e., substrate temperature, precursor concentration, and flow rate, a wide range of exponentially distributed density of localized states profiles and field‐effect mobility values ranging over three orders of magnitude (0.02–30 cm 2 V −1 s −1 ) are obtained for analysis. It is found that mobility can be controlled by appropriately tuning the shape of the density of states profile, increasing the band tail slope and reducing the band edge concentration of shallow states. Most significantly, it is shown that the shape of the density of states can be modified by adjusting the spray‐pyrolysis deposition conditions for electrostatic control. It is found that higher Zn precursor concentration in solution increases the slope of the band tails, leading to higher mobility. Additionally, the band edge concentration is reduced with increased substrate temperature also leading to higher mobility. These results quantify the relationship between defect electrostatics and electron transport while demonstrating electrostatic control via synthetic modification of localized states. Abstract : Spray‐deposited ZnO films are produced with a variety of density of states profiles. Controlled mobility enhancement is demonstrated by synthetically modifying the shape of the density of states: increasing the band tail slope by increasing Zn precursor concentration and reducing the band edge concentration of shallow states by increasing substrate temperature, thus enabling precision design of exceptional conductive oxide electronics.